The British Football Film - Glynn, Stephen (Springer International Publishing, 2018)
This book constitutes the first full volume dedicated to an academic analysis of British football as depicted on film. From early single-camera silents to its current multi-screen mediations, the repeated treatment of football in British cinema points to the game's importance not only in the everyday rhythms of national life but also, and especially, its immutable place in the British imaginary landscape. Through close textual analysis together with production and reception histories, this book explores the ways in which professional footballers, amateur players and supporters (the devoted and the demonized) have been represented on the British screen. As well as addressing the joys and sorrows the game necessarily engenders, British football is shown to function as an accessible structure to explore wider issues such as class, race, gender and even the whole notion of 'Britishness'. .